How chromatin-binding modules interpret histone modifications: lessons from professional pocket pickers - Taverna, Sean D; Li, Haitao; Ruthenburg, Alexander J; Allis, C David; Patel, Dinshaw J (Nature structural & molecular biology, 2007)
Histones comprise the major protein component of chromatin, the scaffold in which the eukaryotic genome is packaged, and are subject to many types of post-translational modifications (PTMs), especially on their flexible tails. These modifications may constitute a 'histone code' and could be used to manage epigenetic information that helps extend the genetic message beyond DNA sequences. This proposed code, read in part by histone PTM–binding 'effector' modules and their associated complexes, is predicted to define unique functional states of chromatin and/or regulate various chromatin-templated processes. A wealth of structural and functional data show how chromatin effector modules target their cognate covalent histone modifications. Here we summarize key features in molecular recognition of histone PTMs by a diverse family of 'reader pockets', highlighting specific readout mechanisms for individual marks, common themes and insights into the downstream functional consequences of the interactions. Changes in these interactions may have far-reaching implications for human biology and disease, notably cancer.